Deep Ocean Gravity Energy Storage: an affordable seasonal energy storage - Hunt, Julian; Nascimento, Andreas; Reus Rodrigues Leite, Joao Paulo; Nascimento, Diego; Tong, Wenxuan; Vasconcelos de Freitas, Marcos Aurelio; Amro, Mohd (Latin American Journal of Energy Research, 2025)
The escalating demand for seasonal energy storage induces the exploration of innovative solutions. Gravitational energy storage systems are a practical solution for storing energy in long cycles, such as seasonal and interannual. This is because the cost of having materials sit at different altitudes is low. This paper proposes and investigates a new technology named Deep Ocean Gravity Energy Storage (DOGES). It operates underwater, utilizing material transported between storage sites on the continental shelf and the ocean floor using cargo ships, underwater cranes, and bucket excavators. This paper presents the methodology, design considerations, and global potential of the proposed technology. Results show that a DOGES plant with a 4 km depth could provide energy storage for 1.3 USD/kWh with a power cost of 4000 USD/kW. Comparisons with other energy storage solutions highlight DOGES as a realistic option for seasonal energy storage and have the potential to support the transition to a decarbonized energy future.